Designing a Model for Administrative Health in the Ministry of Industry, Mine, and Trade - Kiani Anbouhi, Zahra; Rabiei Mondejin, Mohammad Reza; Araei, Vahid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aims to present a model for administrative health in the Ministry of Industry, Mine, and Trade of the country.Methodology: To achieve this goal, a mixed-method research approach was employed. The statistical population in the qualitative section included organizational and academic experts, while the quantitative section included managers and employees involved in the administrative health system of the Ministry of Industry, Mine, and Trade and its provincial offices. In the qualitative section, data were collected through semi-structured interviews, and in the quantitative section, a researcher-made questionnaire was used. The data analysis method in the qualitative section was thematic analysis, and in the quantitative section, structural equation modeling with a partial least squares approach was employed.Findings: The data analysis in the qualitative section led to the formation of the administrative health model in five dimensions, 40 components, and 92 indicators. The data analysis in the quantitative section identified the prioritization of dimensions, components, and indicators of the administrative health model in the Ministry of Industry, Mine, and Trade.Conclusion: According to the results, the prioritization of factors affecting the administrative health in this ministry includes organizational factors, value factors, employee-related factors, managerial factors, and environmental factors, respectively. Based on the obtained results, recommendations were made for achieving administrative health in the Ministry of Industry, Mine, and Trade.